The prevalence of concussion within the military academies: findings from the concussion assessment, research, and education (care) consortium. Issue 11 (25th May 2017) - O'Connor, Kathryn L; Dain Allred, C; Cameron, Kenneth L; Campbell, Darren E; Houston, Megan N; Johnson, Brian R; D'Lauro, Chris; McGinty, Gerald; O'Donnell, Patrick G; Peck, Karen Y; Svoboda, Steven J; McCrea, Michael; et al.
Abstract : Objective : Describe prevalence and risk factors for concussion among USA Service Academy cadets. Design : Prospective. Setting : Three USA Service Academies. Participants : NCAA and non-NCAA athlete cadets (n=7636, 22% female) enrolled in the CARE Consortium (2014–2015). Assessment of risk factors : NCAA status, contact-sport, gender, and brief sensation seeking scale (BSSS) were examined as risk factors for previous concussion. Outcome measures : Number of previous concussions. Main results : 21% of cadets reported a previous concussion with median time from injury being 2.5 years (IQR 0.99–4.57). At least one previous concussion occurred in 18% of freshman prior to Service Academy enrollment and 12% of sophomore through senior cadets sustained a concussion during their time at the academy. Cadets who are NCAA athletes had a 1.57 (95% CI: 1.12–2.19) greater odds of sustaining a concussion at the academy than non-NCAA cadets. Poisson regression modelling the number of previous concussions revealed significant main effects for contact-sport and BSSS. Controlling for BSSS, contact-sport cadets had 1.82 (95% CI: 1.69–1.95) times the prevalence rate of previous concussion compared to non-contact sport athletes. Additionally, controlling for contact-sport, higher BSSS scores increased prevalence of previous concussions by 1.17 (95% CI: 1.10–1.24) times. Conclusions: Overall concussion prevalence among all service academy cadets is similar to prevalence of concussion previously reported for NCAA athletes. Within the academies, cadets who are also NCAA athletes have greater odds of concussion, likely due to increased risk exposure. Contact-sport status and increased sensation seeking is associated with increased number of previous concussions. Competing Interests/ Acknowledgements: This project was supported, in part, with support from the Grand Alliance Concussion Assessment, Research, and Education (CARE) Consortium, funded, in part by the National Collegiate Athletic Association (NCAA) and the Department of Defense (DOD). The U.S. Army Medical Research Acquisition Activity, 820 Chandler Street, Ford Detrick MD 21702–5014 is the awarding and administering acquisition office. This work was supported by the Office of the Assistant Secretary of Defense for Health Affairs through the Psychological Health and Traumatic Brain Injury Program under Award NO W81XWH-14-2-0151. Opinions, interpretations, conclusions and recommendations are those of the author and are not necessarily endorsed by the Department of Defense (DHP funds.)